Persistence of nitrogen oxides emissions using historical time series data: evidence from 37 countries. Issue 4 (2nd October 2022) - Solarin, Sakiru Adebola; Bermejo, Lorenzo; Gil-Alana, Luis A.
ABSTRACT: Two features in time series data: the existence of time trends and the degree of persistence, are examined in this work on the nitrogen oxides emissions from 37 OECD countries. Updated techniques in time series are used that allow for fractional degrees of differentiation in the data. Thus, if the number of differences required is one, nitrogen oxides emissions are not mean reverting in the sense that if there is an exogenous shock (resulting from a technological advancement to change nitrogen oxides emissions), the effect of such shock on nitrogen oxides emissions will be permanent. Time trends are observed in half of the series. For these countries the trend coefficient is found to be positive in all cases. This is an indication that continuous technological progress is needed in taming NOx emissions. In addition to developing their own local technologies, less technologically endowed OECD countries should engage in collaboration with the more technologically endowed countries in order to facilitate increase in trans-border transfer of technology. The technologically advanced countries should also strive to continue to introduce better technologies in a bid to reduce NOx emissions. Most of the results show evidence for persistence of nitrogen oxides emissions.